2019
DOI: 10.1007/s10815-019-01642-3
|View full text |Cite|
|
Sign up to set email alerts
|

A predictive model for women’s assisted fecundity before starting the first IVF/ICSI treatment cycle

Abstract: Purpose To introduce a prognostic model for women's assisted fecundity before starting the first IVF/ICSI treatment cycle. Methods In contrast to previous predictive models, we analyze two groups of women at the extremes of prognosis. Specifically, 708 infertile women that had either a live birth (LB) event in the first autologous IVF/ICSI cycle ("high-assisted-fecundity women", n = 458) or did not succeed in having a LB event after completing three autologous IVF/ICSI cycles ("low-assistedfecundity women", n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Our study also established ‘centre-specific models’ which were based on a single-centre dataset. While several IVF prediction models have been constructed for a similar purpose ( Cai et al , 2011 ; Qiu et al , 2019 ; Vogiatzi et al , 2019 ; Tarin et al , 2020 ; Chen et al , 2022 ; Qu et al , 2022 ; Wang et al , 2022 ), many of them included treatment parameters and intermediate outcomes such as oocyte yield and therefore could not predict the patients’ prognosis before treatment ( Cai et al 2011 ; Vogiatzi et al , 2019 ; Chen et al , 2022 ; Wang et al , 2022 ). A few recent studies reported pretreatment models comparable to ours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study also established ‘centre-specific models’ which were based on a single-centre dataset. While several IVF prediction models have been constructed for a similar purpose ( Cai et al , 2011 ; Qiu et al , 2019 ; Vogiatzi et al , 2019 ; Tarin et al , 2020 ; Chen et al , 2022 ; Qu et al , 2022 ; Wang et al , 2022 ), many of them included treatment parameters and intermediate outcomes such as oocyte yield and therefore could not predict the patients’ prognosis before treatment ( Cai et al 2011 ; Vogiatzi et al , 2019 ; Chen et al , 2022 ; Wang et al , 2022 ). A few recent studies reported pretreatment models comparable to ours.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies are based on validations of random split data, rather than validations in a more recent cohort or other clinics/countries. The work of Tarin et al (2020) included the so-called ‘high-assisted-fecundity women’ who achieved live birth following their first attempt and ‘low-assisted-fecundity women’ who failed to have a live birth after completing three treatment cycles. The model reported an AUC of 0.718 and included a temporal validation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors demonstrated that untreated transient anaesthesia-induced hyperprolactinemia is associated with a lower proportion of fertilized oocytes advancing to cleaving embryos in patients undergoing IVF, although oocyte fertilization and pregnancy rate were unaffected [ 56 ]. Tarín et al developed a predictive model for women’s assisted fecundity before starting the first IVF/ICSI treatment cycle which included prolactin as a prognostic factor which was negatively associated with IVF success [ 73 ].…”
Section: The Relationship Between Prolactin Levels and Art Outcomesmentioning
confidence: 99%
“…In addition, research is directed towards the development of models that can predict IVF/ICSI outcomes. These include female age (Nelson & Lawlor, 2011;Khader et al, 2013;Hamdine et al, 2015;Dhillon et al, 2016;McLernon et al, 2016;Vaegter et al, 2017;Leijdekkers et al, 2018;Metello et al, 2019;Tarín et al, 2020;Wen et al, 2021) and/or ovarian markers (Khader et al, 2013;Hamdine et al, 2015;Dhillon et al, 2016;Leijdekkers et al, 2018;Tarín et al, 2020) as one of their predictors.…”
Section: The Development Of Prediction Modelsmentioning
confidence: 99%